PENELITIAN TINDAKAN KELAS BAGI GURU AGAMA HINDU - Ida Ayu Made Pradnyawati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Teachers, including teachers of the Hindu religion, are often expected to upgrade their practices and learning methods. It is necessary to do this so that the process of learning is contextual. Contextual learning involves modifying the idea of teaching and learning or learning in class according to the creation of thoughts and changes. Situations and circumstances of learning should continually alter. According to these modifications, learning methods and approaches must therefore be established. However, without a well-thought-out strategy, this transition in teaching methods cannot be carried out, and the operational steps must be systematically defined. A study is needed for teachers to understand whether improvements in teaching strategies have been directed following the learning goals and in line with the anticipated learning outcomes. This study is called research into classroom behaviour. In addition to experience as a teacher who had performed classroom action research, this study was carried out based on a literature study on Classroom Action Research—starting from compiling a classroom action research proposal (planning), implementing behaviour, observing and reflection, the classroom action research steps. Observations, data collection, follow-up and classroom action study studies were also performed alongside the action's introduction.